Catalyst for synergistically removing NOx and dioxin as well as preparation method and application of catalyst
Pack the carbon nanochromes through the hydrogenation of hydrogenation of hydrophobic law, and form a CEOBR2 active component through the metharocromide modification, combined with the TIO2 carrier and COO catalyst, to prepare the catalyst of the collaborative removal of NOX and dual villain, and solve the solution In the existing technologies, NOX and Evil Evil are incompletely removed, which realizes high -efficiency pollutants removal and good water anti -sulfur performance.
Patent Information
- Application Number
- CN202411505631.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The existing integrated flue gas pollutant removal process is incomplete in synergistic removal of NOx and dioxins, making it difficult to effectively reduce the emissions of both in thermal power flue gas.
Use the hydrophilic method to treat glucose to obtain carbon nano -balls. As a hard template, it introduces the carbon nano -nanochromes covered with hydroxide crickets, and the CEOBR2 active component is formed through hydrogen bromide. Prepare the catalyst of NOX and dioxide through forming baking.
This catalyst has more than 85 % and 80 % of removal efficiency in NOX and Erxin British in the 150 to 200 ° C interval, and has excellent water anti -sulfur performance and long life, which is suitable for flue gas pollution treatment.
Smart Images

Figure CN119368204A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a catalyst for synergistically removing NOx and dioxins, and belongs to the field of air pollution control. Background Art
[0002] With the rapid development of industrialization and urbanization, the demand for electricity is increasing, and the current conventional thermal power generation technology will emit a large amount of NOx. NOx not only has a strong irritating effect on the human respiratory system and eyes, but may also induce respiratory diseases such as lung disease and asthma, posing a serious threat to public health. In addition, NOx is also a major component of air pollution, which is easy to form haze and acid rain, causing long-term damage to the ecological environment and soil quality. And as one of the greenhouse gases, large-scale emissions of NOx will aggravate global warming and have a profound impact on the earth's ecosystem.
[0003] Selective catalytic oxidation-reduction technology (SCR) is the most mainstream NOx control method at present. 3 Under the action of the catalyst, it is converted into H 2 O and N 2 Patent CN104399453B discloses an SCR denitration catalyst and its preparation method, which uses vanadium molybdenum tungsten oxide as the active component and titanium dioxide, diatomaceous earth and clay as the carrier to prepare a denitration catalyst with large pore size and large specific surface area, which can achieve a denitration activity of more than 95%. Patent CN101716514B discloses a selective denitration catalyst prepared by hydrothermal method and its preparation process, which uses TiO 2 Nanotubes are used as carriers, copper or chromium oxides are used as active components, and tungsten or molybdenum oxides are used as co-catalysts. The catalyst has excellent denitrification activity. At the same time, the presence of tungsten and molybdenum makes SO 2 / SO 3 The conversion rate is reduced. Patent CN104437530B discloses a method for preparing a denitration catalyst. This scheme is a large-scale production scheme. Titanium tungsten powder, adhesive, reinforcing agent, pore-forming agent, active component, peptizing agent, etc. are mixed evenly, and then extruded, dried, and roasted to obtain a finished catalyst. The key to this scheme lies in the ratio of each raw material. The finished catalyst has excellent structural strength and denitration performance.
[0004] In the flue gas of thermal power generation, especially the flue gas of waste incineration thermal power generation, there is not only a large amount of NOx, but also a high content of dioxin. Dioxin is a highly toxic and highly carcinogenic substance. Short-term exposure to dioxin may cause skin damage and liver dysfunction, while long-term exposure may cause serious health problems such as immune system disorders, endocrine system disorders and cancer. Patent CN103657638B discloses an integral dioxin removal catalyst and its preparation method, which uses honeycomb ceramics as a carrier and V 2 O 5 , WO 3 and TiO 2 The catalyst can achieve a conversion rate of more than 95% at 160-180°C, and has high strength and tightly bound active components. For example, patent CN104324717B discloses a catalyst for removing dioxins from waste incinerator exhaust gas and its preparation method, using honeycomb TiO 2 The catalyst is a carrier, and one or more of vanadium, tungsten, silver, copper, manganese, iron, nickel, strontium, and cesium are used as active elements. The catalyst contains a large number of micropores, which increases the specific surface area of the catalyst, thereby improving the activity of the catalyst.
[0005] In view of the serious hazards of NOx and dioxins, effective measures must be taken to reduce their emissions and strengthen their monitoring and management in the environment. At present, the integrated pollutant removal process has become a research and development hotspot for controlling flue gas pollution in various countries. For example, patents CN108421390B, CN110773191B, and CN109603804B disclose some solutions for the synergistic removal of NOx and dioxins. However, the current integrated removal process for flue gas pollutants is still imperfect. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a catalyst for synergistically removing NOx and dioxins in view of the current immature technology for integrated removal of flue gas pollutants.
[0007] The purpose of the present invention can be achieved through the following technical scheme: a preparation method of a catalyst for synergistic removal of NOx and dioxins, which first uses a hydrothermal method to treat glucose to obtain carbon nanospheres, and then uses the carbon nanospheres as a hard template to introduce an active component cerium element. Since the surface of the carbon nanospheres is rich in hydroxyl groups, cerium ions are adsorbed on the spherical surface. By adjusting the pH to an alkaline environment, cerium hydroxide-coated carbon nanospheres are formed. Then, hydrogen bromide is used as a modifier, and the collected cerium hydroxide-coated carbon nanospheres are treated by a hydrothermal method. In order to prevent the loss of hydrogen bromide, a layer of oil film protection layer is also added, and bromide ions replace part of the anions under high temperature and high pressure conditions. Finally, a carrier, a co-catalyst, etc. are introduced, and the finished catalyst can be obtained by molding and calcining. Due to the replacement of Br ions, part of CeO 2 Transformation to CeOBr2 , increasing the acidity of the active components, thereby inhibiting the deposition of sulfides on the surface of the active components. The co-catalyst CoO has strong redox ability and can convert dioxins into non-toxic or low-grade small molecules.
[0008] A catalyst for synergistic removal of NOx and dioxins, the catalyst is TiO 2 As the carrier, hollow spherical CeOBr 2 The active component is CoO and the co-catalyst is CoO. Based on the mass of the carrier, the mass percentage of the active component is 1-10%, and the mass percentage of the co-catalyst is 1-10%.
[0009] Among the above catalysts: a catalyst for synergistic removal of NOx and dioxins, characterized in that: based on the mass of the carrier, the mass percentage of the active component is 5-8%, and the mass percentage of the co-catalyst is 3-5%.
[0010] A method for preparing the above-mentioned synergistic NOx and dioxin removal catalyst, the steps of the method are as follows:
[0011] (1) Preparation of carbon nanospheres: preparing a glucose solution, transferring the solution to a reactor for hydrothermal reaction to synthesize carbon nanospheres, and then centrifuging, washing, and drying for later use;
[0012] (2) Preparation of hollow cerium oxide spheres:
[0013] S1: dissolving cerium salt in deionized water to prepare a solution, then dispersing the carbon nanospheres obtained in step (1) in the solution, stirring to allow the carbon nanospheres to adsorb cerium ions, adding ammonia water to adjust the alkalinity and continuing stirring for 2 to 4 hours, filtering, washing, and drying for later use;
[0014] S2: preparing a hydrogen bromide solution, dispersing the powder obtained in step S1 in the solution, then adding an oil film isolation layer to the solution, transferring the solution to a reactor for hydrothermal treatment, then filtering, washing, and drying, and the obtained powder is ready for use;
[0015] (3) Preparation of the catalyst: titanium dioxide, the powder obtained in step (2), and a binder are uniformly mixed to obtain a mixed powder, and then a cobalt salt solution is added to the mixed powder, stirred and refined, and finally thoroughly dried and transferred to an atmosphere furnace for calcination to obtain a finished catalyst.
[0016] In the above preparation method: the concentration of the glucose solution in step (1) is 0.7-0.9M; the hydrothermal temperature is 180-200°C, and the hydrothermal time is 4-6h; and the drying method is freeze-drying.
[0017] In the above preparation method: the cerium salt described in step S1 is cerium nitrate or cerium chloride, and the concentration of the cerium salt solution is 0.25-0.5M; the mass of carbon nanospheres added is 5-10% of the mass of the solution; and the carbon nanospheres need to be stirred for 4-8 hours to adsorb cerium ions.
[0018] In the above preparation method: in step S1, the pH value is adjusted to 9-10 with aqueous ammonia, and the drying method is freeze-drying.
[0019] In the above preparation method: the concentration of the hydrogen bromide solution in step S2 is 2-4wt%, and the mass ratio of the powder obtained in step S1 to the solution is (5-10):100;
[0020] The oil film isolation layer described in step S2 is palmitic acid or octadecenoic acid, and the mass ratio of the oil film isolation layer to the hydrogen bromide solution is (1-2):100.
[0021] In the above preparation method: the hydrothermal reaction temperature in step S2 is 140-160° C., and the hydrothermal time is 4-6 hours; and the drying method is freeze-drying.
[0022] In the above preparation method: the binder in step (3) is polyethylene oxide or sodium carboxymethyl cellulose, and the added mass of the binder is 3-5% of the titanium dioxide; the cobalt salt is cobalt nitrate;
[0023] The calcination atmosphere in step (3) is N 2 atmosphere, the calcination temperature is 400-450°C, and the calcination time is 4-6h.
[0024] In the technical solution of the present invention, the application of the catalyst in the synergistic removal of NOx and dioxins in flue gas is preferably in the application temperature range of 150-200°C.
[0025] Beneficial effects:
[0026] The invention discloses a method for preparing a catalyst for synergistically removing NOx and dioxins. The catalyst is based on TiO 2 As the carrier, hollow spherical CeOBr 2 The key to this scheme is the hollow spherical CeOBr 2 The hollow spherical structure not only increases the specific surface area of the catalyst, but also has a unique pore effect that can improve the catalytic activity. 2 Some of the oxygen ions in the catalyst are replaced by bromide ions, thereby increasing the surface acidity of the catalyst and reducing the SO in the low-temperature flue gas. 2 / SO 3The deposition on the catalyst surface can also enhance the catalyst's ability to capture ammonia. The catalyst has extremely high removal efficiency for both NOx and dioxins in the range of 150-200°C, with a NOx removal efficiency of more than 85% and a dioxin removal efficiency of more than 80%. The catalyst has excellent denitrification and dioxin removal efficiency, excellent water-sulfur resistance, long life, high economic value and broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the denitration activity diagram of the embodiment and the comparative example;
[0028] Figure 2 Dioxin removal efficiency diagram of the embodiment and comparative example;
[0029] Figure 3 Water and sulfur resistance performance diagram of Example 3 and Comparative Example 2. DETAILED DESCRIPTION
[0030] The following examples further illustrate the preparation method of the catalyst for synergistically removing NOx and dioxins of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0031] Catalytic performance test: The catalyst was crushed, 20-40 mesh particles were screened and 2 ml were transferred to the middle of the quartz reactor. The catalyst was fixed on both sides with quartz wool. One end of the quartz reactor was connected to simulated flue gas (NO (600ppm), NH 3 (600ppm), O 2 (6 vol%), chlorobenzene (100 ppm, chlorobenzene was used to simulate dioxins), N 2 As carrier gas, GHSV is 8000h -1 ), and the other end is connected to a flue gas analyzer to detect the concentration of NO and chlorobenzene in the exhaust gas. The temperature of the quartz reactor is controlled at 150-200°C, and the exhaust gas concentration is detected by staying at 10°C for 30 minutes.
[0032] Water and sulfur resistance test: The catalyst was crushed, 20-40 mesh particles were screened and 2 ml were transferred to the middle of the quartz reactor. The catalyst was fixed on both sides with quartz wool. One end of the quartz reactor was connected to simulated flue gas (NO (600ppm), NH 3 (600ppm), O 2 (6 vol%), SO 2 (25ppm), chlorobenzene (100ppm, chlorobenzene is used to simulate dioxins), deionized water (2ml / min), N 2 As carrier gas, GHSV is 8000h -1), and the other end is connected to a flue gas analyzer to detect the concentration of NO and chlorobenzene in the exhaust gas. The temperature of the quartz reactor is controlled at 150°C, and the reaction is continued for 100 hours, and the exhaust gas concentration is detected every 1 hour.
[0033] Example 1
[0034] Prepare a 0.7M glucose solution, hydrothermally treat it at 200℃ for 4h, then centrifuge, wash, freeze-dry and obtain carbon nanosphere powder. Prepare a 0.25M cerium nitrate solution, then disperse 8wt% of the solution mass of carbon nanosphere powder in it and stir for 6h. Adjust the pH to 9 with ammonia water, continue stirring for 2h, filter, wash, freeze-dry and set aside. Prepare a 2wt% hydrogen bromide solution, then disperse the powder obtained in the previous step in the solution, and add 8% of the solution mass. Add palmitic acid to the solution in an amount of 1% of the solution mass, then transfer it to a hydrothermal kettle and treat it at 150℃ for 4h, centrifuge, wash, freeze-dry and obtain the powder for use. Weigh titanium dioxide, 4% polyethylene oxide by mass of titanium dioxide and the powder obtained in the previous step (according to CeOBr 2 The titanium dioxide was mixed with cobalt nitrate (CoO loading 6%), and cobalt nitrate (CoO loading 3%) was dissolved in deionized water to prepare a solution, the deionized amount was 50% of the mass of titanium dioxide, and then the solution and powder were mixed evenly, stirred and refined. After thorough drying, it was transferred to an atmosphere furnace and calcined at 450°C for 5h under a nitrogen atmosphere to obtain a finished catalyst.
[0035] Example 2
[0036] Prepare a 0.9M glucose solution, hydrothermally treat it at 180℃ for 5h, then centrifuge, wash, freeze-dry and obtain carbon nanosphere powder. Prepare a 0.35M cerium chloride solution, then disperse 5wt% of the solution mass of carbon nanosphere powder in it and stir for 7h. Adjust the pH to 10 with ammonia water, continue stirring for 3h, filter, wash, freeze-dry and set aside. Prepare a 4wt% hydrogen bromide solution, then disperse the powder obtained in the previous step in the solution, and the addition amount is 5% of the solution mass. Add octadecenoic acid to the solution, the addition amount is 2% of the solution mass, then transfer it to a hydrothermal kettle and treat it at 150℃ for 5h, centrifuge, wash, freeze-dry and obtain the powder for use. Weigh titanium dioxide, 3% sodium carboxymethyl cellulose by mass of titanium dioxide and the powder obtained in the previous step (according to CeOBr 2 Cobalt nitrate (CoO loading 5%) was dissolved in deionized water to prepare a solution, the deionized amount was 55% of the mass of titanium dioxide, and then the solution and powder were mixed evenly, stirred and refined. After thorough drying, it was transferred to an atmosphere furnace and calcined at 425℃ for 5h under nitrogen atmosphere to obtain the finished catalyst.
[0037] Example 3
[0038] Prepare a 0.8M glucose solution, hydrothermally treat it at 180℃ for 6h, then centrifuge, wash, freeze-dry and obtain carbon nanosphere powder. Prepare a 0.4M cerium chloride solution, then disperse 10wt% of the solution mass of carbon nanosphere powder in it, and stir for 4h. Adjust the pH to 9 with ammonia water, continue stirring for 4h, filter, wash, freeze-dry and set aside. Prepare a 4wt% hydrogen bromide solution, then disperse the powder obtained in the previous step in the solution, and add 6% of the solution mass. Add palmitic acid to the solution in an amount of 1.5% of the solution mass, then transfer it to a hydrothermal kettle and treat it at 140℃ for 5h, centrifuge, wash, freeze-dry and obtain the powder for use. Weigh titanium dioxide, 3% polyethylene oxide by mass of titanium dioxide and the powder obtained in the previous step (according to CeOBr 2 The titanium dioxide was mixed with cobalt nitrate (CoO loading 7%), and cobalt nitrate (CoO loading 4%) was dissolved in deionized water to prepare a solution, the deionized amount was 60% of the mass of titanium dioxide, and then the solution and powder were mixed evenly, stirred and refined. After thorough drying, it was transferred to an atmosphere furnace and calcined at 425℃ for 4h under nitrogen atmosphere to obtain the finished catalyst.
[0039] Example 4
[0040] Prepare a 0.7M glucose solution, hydrothermally treat it at 190℃ for 4h, then centrifuge, wash, and freeze-dry to obtain carbon nanosphere powder. Prepare a 0.5M cerium nitrate solution, then disperse 6wt% of the carbon nanosphere powder in it and stir for 8h. Adjust the pH to 10 with ammonia water, continue stirring for 2h, filter, wash, and freeze-dry for use. Prepare a 3wt% hydrogen bromide solution, then disperse the powder obtained in the previous step in the solution, and the addition amount is 10% of the solution mass. Add octadecenoic acid to the solution in an amount of 1.5% of the solution mass, then transfer it to a hydrothermal kettle and treat it at 160℃ for 6h, centrifuge, wash, and freeze-dry to obtain the powder for use. Weigh titanium dioxide, 5% sodium carboxymethyl cellulose by mass of titanium dioxide, and the powder obtained in the previous step (according to CeOBr 2 The catalyst was prepared by mixing the cobalt nitrate (CoO loading 8%) and dissolving it in deionized water to prepare a solution. The deionized water dosage was 55% of the mass of the titanium dioxide. The solution and the powder were mixed evenly and stirred to make mud. After being thoroughly dried, the mixture was transferred to an atmosphere furnace and calcined at 400°C for 6 hours under a nitrogen atmosphere to obtain a finished catalyst.
[0041] Comparative Example 1
[0042] Prepare a 0.4M cerium chloride solution, adjust the pH to 9 with ammonia water, stir for 4 hours, filter, wash, freeze-dry and set aside. Prepare a 4% hydrogen bromide solution, and then disperse the powder obtained in the previous step in the solution, with the addition amount being 6% of the solution mass. Add palmitic acid to the solution, with the addition amount being 1.5% of the solution mass, and then transfer it to a hydrothermal kettle and treat it at 140°C for 5 hours, centrifuge, wash, freeze-dry and set aside. Weigh titanium dioxide, 3% polyethylene oxide by mass of titanium dioxide and the powder obtained in the previous step (according to CeOBr 2 The titanium dioxide was mixed with cobalt nitrate (CoO loading 7%), and cobalt nitrate (CoO loading 4%) was dissolved in deionized water to prepare a solution, the deionized amount was 60% of the mass of titanium dioxide, and then the solution and powder were mixed evenly, stirred and refined. After thorough drying, it was transferred to an atmosphere furnace and calcined at 425℃ for 4h under nitrogen atmosphere to obtain the finished catalyst.
[0043] Comparative Example 2
[0044] Prepare a 0.8M glucose solution, hydrothermally treat it at 180℃ for 6h, then centrifuge, wash, freeze-dry and obtain carbon nanosphere powder. Prepare a 0.4M cerium chloride solution, then disperse 10wt% of the solution in it and stir for 4h. Adjust the pH to 9 with ammonia water, continue stirring for 4h, filter, wash, freeze-dry and set aside. Weigh titanium dioxide, 3% polyethylene oxide by mass of titanium dioxide and the powder obtained in the previous step (CeO 2 The titanium dioxide was mixed with cobalt nitrate (CoO loading 7%), and cobalt nitrate (CoO loading 4%) was dissolved in deionized water to prepare a solution, the deionized amount was 60% of the mass of titanium dioxide, and then the solution and powder were mixed evenly, stirred and refined. After thorough drying, it was transferred to an atmosphere furnace and calcined at 425℃ for 4h under nitrogen atmosphere to obtain the finished catalyst.
[0045] Comparative effect: Taking Example 3 as a reference, Comparative Example 1 omitted the preparation of carbon nanospheres and used them as templates to synthesize hollow spherical CeOBr 2 This will cause the specific surface area of the active components to decrease and the pore effect to weaken, resulting in a decrease in denitrification activity. 2 It also participates in the degradation of chlorobenzene, resulting in a decrease in the removal efficiency of chlorobenzene. In Comparative Example 2, the bromide ion substitution was cancelled, the surface acidity of the catalyst decreased, the water and sulfur resistance decreased, and the NH 3 The capture capacity of the gas is reduced, resulting in a decrease in the degradation performance of NOx and chlorobenzene.
Claims
1. A catalyst for synergistically removing NOx and dioxins, characterized in that: The catalyst uses TiO2 as a carrier, hollow spherical CeOBr2 as an active component and CoO as a co-catalyst. Based on the mass of the carrier, the mass percentage of the active component is 1-10%, and the mass percentage of the co-catalyst is 1-10%.
2. The synergistic NOx and dioxin removal catalyst according to claim 1, characterized in that: Based on the mass of the carrier, the mass percentage of the active component is 5-8%, and the mass percentage of the co-catalyst is 3-5%.
3. A method for preparing the catalyst for synergistic removal of NOx and dioxins according to claim 1, characterized in that: The steps of this method are as follows: (1) Preparation of carbon nanospheres: preparing a glucose solution, transferring the solution to a reactor for hydrothermal reaction to synthesize carbon nanospheres, and then centrifuging, washing, and drying for later use; (2) Preparation of hollow cerium oxide spheres: S1: dissolving cerium salt in deionized water to prepare a solution, then dispersing the carbon nanospheres obtained in step (1) in the solution, stirring to allow the carbon nanospheres to adsorb cerium ions, adding ammonia water to adjust the alkalinity and continuing stirring for 2 to 4 hours, filtering, washing, and drying for later use; S2: preparing a hydrogen bromide solution, dispersing the powder obtained in step S1 in the solution, then adding an oil film isolation layer to the solution, transferring the solution to a reactor for hydrothermal treatment, then filtering, washing, and drying, and the obtained powder is ready for use; (3) Preparation of the catalyst: titanium dioxide, the powder obtained in step (2), and a binder are uniformly mixed to obtain a mixed powder, and then a cobalt salt solution is added to the mixed powder, stirred and refined, and finally thoroughly dried and transferred to an atmosphere furnace for calcination to obtain a finished catalyst.
4. The preparation method according to claim 3, characterized in that: The concentration of the glucose solution in step (1) is 0.7-0.9M; the hydrothermal temperature is 180-200°C, the hydrothermal time is 4-6h; and the drying method is freeze drying.
5. The preparation method according to claim 3, characterized in that: The cerium salt described in step S1 is cerium nitrate or cerium chloride, and the concentration of the cerium salt solution is 0.25-0.5M; the mass of carbon nanospheres added is 5-10% of the mass of the solution; and the stirring time is 4-8h.
6. The preparation method according to claim 1, characterized in that: In step S1, the pH value is adjusted to 9-10 with aqueous ammonia, and the drying method is freeze-drying.
7. The preparation method according to claim 1, characterized in that: The concentration of the hydrogen bromide solution in step S2 is 2-4 wt %, and the mass ratio of the powder obtained in step S1 to the solution is (5-10):100; The oil film isolation layer described in step S2 is palmitic acid or octadecenoic acid, and the mass ratio of the oil film isolation layer to the hydrogen bromide solution is (1-2):
100.
8. The preparation method according to claim 1, characterized in that: The hydrothermal reaction temperature in step S2 is 140-160° C., and the hydrothermal time is 4-6 hours; and the drying method is freeze drying.
9. The preparation method according to claim 1, characterized in that: The binder in step (3) is polyethylene oxide or sodium carboxymethyl cellulose, and the added mass of the binder is 3-5% of the titanium dioxide; the cobalt salt is cobalt nitrate; The calcination atmosphere in step (3) is N2 atmosphere, the calcination temperature is 400-450°C, and the calcination time is 4-6h.
10. Use of the catalyst according to claim 1 in the synergistic removal of NOx and dioxins in flue gas, preferably: the application temperature range is 150-200°C.
Citation Information
Patent Citations
Selective denitrification catalyst prepared by hydrothermal method and preparation process thereof
CN101716514B
Monolithic dioxin removal catalyst and its preparation method
CN103657638B
Catalysts for removing dioxins from waste incinerator exhaust gas and their preparation methods
CN104324717B
A kind of SCR denitration catalyst and preparation method thereof
CN104399453B
A kind of preparation method of denitrification catalyst
CN104437530B